The Effect of Personal Cost and Bystander Effect As Moderating Variable on Whistleblowing Intention - Christa Alethea; David Adechandra Ashedica Pesudo, S.E., M.Ak (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
This study aims to determine the effect of personal cost on whistleblowing intention with the bystander effect as a moderating variable. The population in this study were students of the Faculty of Economics and Business, W University who are active in organization. The data analysis technique used is moderated regression analysis. The result of this study indicate that personal cost has a negative effect on whistleblowing intention and bystander effect has a negative effect which strengthens the negative effect of personal cost on whistleblowing intention.